Ответы 2

  • x {}^{2}  + 17x  + 52 = 0 \\  {x}^{2}  + 13x + 4x + 52 = 0 \\ x \times (x + 13) + 4(x + 13) = 0 \\ (x + 13) \times (x + 4) = 0 \\ x + 13 = 0 \\ x + 4 = 0 \\ x =  - 13 \\ x =  - 4x1 =  - 13 \\  \\ x2 =  - 4 Удачи!
    • Автор:

      scout0juh
    • 5 лет назад
    • 0
  •  {x}^{2}  + 17x + 52 = 0 \\  {x}^{2}  + 13x + 4x + 52 = 0 \\ x \times (x + 13) + 4 \times (x - + 13) = 0 \\ (x + 13) \times (x + 4) = 0 \\ x + 13 = 0 \\ x + 4 = 0 \\ x =  - 13 \\ x =  - 4 \\ x1 =  - 13 \\ x2 =  - 4
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years